Chronicles of a Cairo bookseller - Wassef, Nadia (London : Corsair, 2021)
"The warm and winning story of starting a bookstore where there were none, Shelf Life recounts Nadia Wassef's troubles and triumphs as founder and manager of Cairo-based Diwan"--
Prologue -- The Café -- Egypt Essentials -- Cookery -- Business and Management -- Pregnancy and Parenting -- The Classics -- Art and Design -- Self-Help -- Epilogue.
Keywords: Wassef, Nadia; Diwan (Bookstore : Zamalek, Cairo, Egypt); Booksellers and bookselling -- Egypt -- Cairo -- Biography; Bookstores -- Egypt -- Cairo